2000
DOI: 10.1016/s0022-5347(05)67523-4
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence and Progression of Stage T1, Grade 3 Transitional Cell Carcinoma of the Bladder Following Intravesical Immunotherapy With Bacillus Calmette-Guerin

Abstract: Adjuvant immunotherapy with BCG after complete transurethral resection of bladder tumor represents a highly effective primary treatment of stage pT1, grade 3 carcinoma of the bladder. Immediate radical cystectomy does not appear necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(27 citation statements)
references
References 33 publications
1
23
0
1
Order By: Relevance
“…25,26 The literature contains many reports of prophylactic effects of anticancer drugs on superficial bladder cancers, [27][28][29] but long-term follow-up suggests that efficacy does not persist for many years. 9 The prophylactic effects of BCG, on the other hand, are reported to extend over very long periods, [19][20][21] including, in one report, a follow-up of greater than 10 years. 30 Several trials of therapy with BCG in combination with anticancer drugs have been conducted, but the results have generally been controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25,26 The literature contains many reports of prophylactic effects of anticancer drugs on superficial bladder cancers, [27][28][29] but long-term follow-up suggests that efficacy does not persist for many years. 9 The prophylactic effects of BCG, on the other hand, are reported to extend over very long periods, [19][20][21] including, in one report, a follow-up of greater than 10 years. 30 Several trials of therapy with BCG in combination with anticancer drugs have been conducted, but the results have generally been controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Although the anticancer mechanisms of BCG are not totally understood, they are generally considered to involve immunological reactions. [14][15][16][17][18] Clinically, superficial bladder cancer is highly sensitive to BCG, [19][20][21][22] and it is generally well established that stimulation of the immune system exerts only beneficial effects on tumor development. In contrast, anticancer drugs may sometimes act as tumor-promoting agents, both in animal experiments 23 and in human cases, 24 at least partly as a result of immunological damage.…”
Section: Discussionmentioning
confidence: 99%
“…This rate is only 50% to 60% if cystectomy is not performed until recurrence. However, the question is raised as to whether these good results could also be achieved through conservative adjuvant therapy, preserving the bladder and, thus, maintaining a markedly improved quality of life, and whether radical cystectomy could be restricted to a minority of patients [14]. Treatment of patients with T1G3 bladder tumors has not been well defined because of the shortage of clinical trials with careful selection of patients and the difficulty of conducting prospective randomized trials with a tumor generally acknowledged today to need adjuvant therapy after TURBT.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 13 [10][11][12][13][14][15][16][17][18][19][20][21][22] publications or abstracts, the trials of which met the selection criteria, were identified. The publication date of the trials ranged from 2000 to 2005.…”
Section: Trial and Patient Characteristicsmentioning
confidence: 99%
“…this approach offers superior prevention of recurrence and progression in high-risk patients compared to tUrBt alone [9][10][11][12][13]. However, Bcg can have toxicities including urinary frequency and chemical cystitis as well as more severe side effects like fever, prostatitis, liver toxicity, and Bcg sepsis [14,15].…”
Section: Introductionmentioning
confidence: 99%